On multistabilities of real car's wake. Issue 164 (May 2017) - Bonnavion, G.; Cadot, O.; Évrard, A.; Herbert, V.; Parpais, S.; Vigneron, R.; Délery, J.
Abstract: Two different cases of wake transitions are identified with two car models in real flow condition, a hatchback vehicle (Renault Mégane) and a light van (Renault Kangoo). Their wakes are studied thanks to aerodynamic forces and pressure distributions at the car's base. For the hatchback car, a transition yawing angle of ± 8.6 ° at which a bistable behavior occurs is identified. It originates from a massive intermittent reattachment occurring simultaneously on the whole slanted rear window. The reattachment is suspected to be caused by the increase in curvature of the separated shear layer as the yaw increases. For the van, reversals of the base pressure distribution are observed for a smaller yawing angle of ± 4 ° excluding unambiguously the possibility of a reattachment because of the bluntness of the after-body. A bistable regime between the two reversed states is studied at a yawing angle of 4 ° . It is supposed to be caused by a wake instability recently evidenced for the simplified square back Ahmed body that leads to the presence of two distinct static modes of the wake. It is shown that both modes can be permanently selected independently from the bistable configuration. Abstract : Highlights: Bistable wake behaviors are detected for two real cars for small yawing angles. Bistability is due to an intermittent flow reattachment for the hatchback car. Bistability is due to wake instability for the van. The two stable states may differ in lift by 23% and 27%. The two stable states may differ by 0% and 5% in drag.